Biosignal Processing Fundamentals and Recent Applications with MATLAB ® - Bernhard, Stefan (De Gruyter Textbook, 2022)
This book explains the principles of biosignal processing and its practical applications using MATLAB. Topics include the emergence of biosignals, electrophysiology, analog and digital biosignal processing, signal discretization, electrodes, time and frequency analysis, analog and digital filters, Fourier-transformation, z-transformation, pattern recognition, statistical data analysis, physiological modelling and applications of EEG, ECG, EMG, PCG and PPG signals. Additional scientifi c contributions on motion analysis by guest authors Prof. Dr. J. Subke and B. Schneider as well as classification of PPG signals by Dr. U. Hackstein.